SCIENTIFIC JUSTIFICATION AND TECHNOLOGIES FOR CREATION OF DAIRY CLUSTER IN ISSYK-KUL PROVINCE (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2022)
The given article is considered as analysis of possibility to create dairy clusterin Issyk-Kul province within the Kyrgyz Republic Presidential Decree #1 of January 11, 2019«On declaring 2019 the year of regional development and digitalization of the country» and«Biotechnological cluster Ural-Eurasia»
Keywords: dairy cluster, EKO (Eurasian Cluster Observatory), cluster core, roadmap.